Performance and Transcriptional Response of the Green Peach Aphid Myzus persicae to the Restriction of Dietary Amino Acids - Wu, Jun; Lan, Hao; Zhang, Zhan-Feng; Cao, He-He; Liu, Tong-Xian (Frontiers in Physiology, 2020)
Free amino acids in the phloem sap are the dominant nitrogen source for aphids, but their availability is usually poor. Although some studies have explored the effect of dietary amino acid restriction on aphid performance, little is known about the molecular basis of these effects. Here, we examined the performance and transcriptome of the green peach aphid, Myzus persicae, fed a standard diet (Control diet) or a diet containing 50% of the total amino acids of the Control diet (Half diet). Aphid weight and fecundity were significantly reduced in the Half diet group. Transcriptomic analysis showed that a total of 1460 genes were differentially expressed between the groups fed on the two diets, which many of them were associated with nutrient and energy metabolism. When feeding the Half diet, aphids upregulated genes associated with the amino acid biosynthetic pathway (predominantly amino acid biosynthesis genes and some amino acid transporter genes) as well as the cysteine and serine protease genes. Furthermore, these aphids displayed increased expression of genes associated with glycolysis, which could generate intermediates for de novo amino acid biosynthesis. Consistent with this, elevated glucose levels were observed in aphids in the Half diet group. Additionally, the expression levels of several genes associated with hormonal signaling pathway were altered. Several genes related to juvenile hormone and insulin-like peptide signaling were downregulated, including Krüppel homolog 1 (Kr-h1) and insulin-like pepetide 5 (Ilp5), respectively. In contrast, several genes related to ecdysone signaling were upregulated including broad-complex core protein (Br-c) and shade (Shd). Despite their poor performances, M. persicae adapted to dietary restriction of amino acids, through upregulation of genes involved in amino acid biosynthesis, glycolysis, and protein degradation, as well as by altering the expression level of genes involved in hormone signaling pathways.